Monitoring joint health in haemophilia: Factors associated with deterioration. Issue 6 (5th September 2017) - Kuijlaars, I. A. R.; Timmer, M. A.; de Kleijn, P.; Pisters, M. F.; Fischer, K.
Abstract : Introduction: Joint bleeds in patients with haemophilia may result in haemophilic arthropathy. Monitoring joint health is essential for identifying early signs of deterioration and allows timely adjustment of treatment. Aim: The aim was to describe changes in joint health over 5‐10 years follow‐up and identify factors associated with joint health deterioration in patients with haemophilia. Methods: A post hoc analysis was performed from previous cohort studies in patients with moderate/severe haemophilia, ≥16 years. Joint health of ankles, knees and elbows was measured with the Haemophilia Joint Health Score (HJHS) from 2006‐2008 (T0) to 2011‐2016 (T1). Analyses were performed on patient level (ΔHJHS‐total) and joint level (ΔHJHS‐joint). Deterioration was defined as ΔHJHS‐total ≥4 and ΔHJHS‐joint ≥2. Results: Sixty‐two patients (median age 25, 73% severe haemophilia, median [interquartile range] 0.0 [0.0;2.0] joint bleeds between T0 to T1) were included. After median 8 years, HJHS‐total deteriorated in 37% and HJHS‐joint in 17%. Ankle joints (31%) showed deterioration more often than elbows (19%) and knees (3%). Deterioration of HJHS‐total was only associated with severe haemophilia. Deterioration of HJHS‐joint was weakly associated with a lower HJHS at baseline and more self‐reported limitations in activities, and strongly with more joint bleeds between T0 and T1 and presence of synovitis. Conclusion: In 37% of patients with moderate/severe haemophilia and low joint bleeding rates, joint health deteriorated over 5‐10 years. Ankle and elbow joints showed deterioration most frequently. Factors found in this study help to identify which joints need frequent monitoring in patients with haemophilia with access to early prophylaxis.